An innovative design of mega shaft boring machine (SBM) cutterhead based on TRIZ and AD theory. (February 2023) - Xiao, Jing; Liu, Feixiang; Yang, Mei; Ke, Wei; Liu, Dong; Lin, Laikuang
Cutterhead is the key component of the mega shaft boring machine (SBM), whose complex structure and huge size lead to high manufacturing difficulty and cost, and its reliability is difficult to guarantee under huge loads. It is difficult to design the cutterhead only referring to the existing small horizontal tunnel boring machine cutterhead. In order to brainstorm innovative ideas, the paper incorporates the TRIZ into AD to address the following issues. Firstly, engineering conflicts in designing process are eliminated by TRIZ tools to generating innovative ideas. Then, the decomposition of functional requirements and design parameters are employed based on independence axiom of AD, transferring the abstract ideas into concrete design solutions. Moreover, fuzzy comprehensive evaluation is adopted to choose a better design scheme from alternatives of critical component. Finally, the feasibility and practicality of the proposed approach has been demonstrated through case study of designing a novel mega SBM cutterhead. The cutterhead structure is significantly improved with embedded movable cutter boxes, which can excavate step by step to reduce the driving torque, and the manufacturing and transportation cost has been greatly reduced. The method can help designer to innovative design the key components of large-scale underground tunneling equipment.